Relationship between economical and sociodemographic health indicators and social development with COVID-19 mortality in the first 120 days of the pandemic - Ferrándiz Espadin, Renato (2021)
Objective: To describe mortality of COVID-19 in relationship with social aspects, economical and sociodemographic indicators of health of the first countries affected at the beginning of the pandemic. Methods: A longitudinal descriptive study was carried-out, 63 countries affected at different magnitude were selected and followed from the first day they declare the first patient until May 31st 2020 with data gathered from WHO, PAHO, KNOEMA, DATOS MACRO, INDEX MUNDI and from the Johns Hopkins University. Results: At 60-days the mean day of conformation of the first case correlated with mortality, at 75-days of the pandemic obesity correlated with mortality. Conclusions: At the beginning of the pandemic, societies with higher life expectancies, where obese people and people with significant co-morbidities predominate, had higher mortality rates compared to less developed countries where transmissible diseases predominate. Fatal outcomes occur despite of having abundant economical resources, revealing the existence of elements that inevitable led to negative outcomes.